Algoritma Keadilan : Resiko dan Peluang Penggunaan AI oleh Hakim Pengadilan - Arbani, Tri Suhendra (IAIN Metro, 2025)
This research aims to analyze the ethical and legal challenges of using Artificial Intelligence (AI) in judicial systems, with a specific focus on Indonesia. It seeks to explore the risks, opportunities, and implications of AI in judicial decision-making, emphasizing the importance of balancing efficiency with fairness and accountability. The study employs a normative legal research approach with a conceptual framework and prescriptive analysis. It includes a comparative analysis of global practices and theoretical frameworks to contextualize AI’s use within Indonesia's judicial landscape. This research highlights a unique focus on the intersection of algorithmic justice and the Indonesian judiciary, addressing the current lack of regulatory and ethical frameworks in AI adoption for judicial decision-making. It also proposes practical solutions to integrate AI responsibly while maintaining judicial integrity. The findings indicate that AI can significantly improve judicial efficiency and reduce case backlogs. However, risks such as algorithmic bias, ethical dilemmas, and legal uncertainties must be addressed. Comparative insights from countries like Singapore and Estonia underscore the necessity for clear regulations and ethical safeguards.The study concludes that Indonesia must adopt a balanced approach to integrate AI into its judiciary. Robust legal frameworks, ethical oversight, and adaptive evaluations of AI systems are critical to ensuring AI's role in promoting fairness, accountability, and public trust in judicial processes.